2011
DOI: 10.1177/0148607110382023
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐3–Enriched Lipid Emulsion for Liver Salvage in Parenteral Nutrition–Induced Cholestasis in the Adult Patient

Abstract: The intrahepatic cholestasis attributed to parenteral nutrition (PN) in the adult patient is relatively rare and usually occurs in patients receiving long-term PN. This article reports the first case of an adult patient with cholestatic PN-associated liver disease without sepsis who received almost all her nutrition requirements through PN. Administration of an ω-3-enriched lipid emulsion added to the PN regimen reversed cholestasis and demonstrated histologic improvement on serial liver biopsy. The patient ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 24 publications
0
19
0
3
Order By: Relevance
“…Although the cost of omega-3 supplementation varies by dose, frequency, route of administration, and choice of formula, the leading parenteral formula used in this meta-analysis (Omegaven) has been reported to cost up to 3 times more than another lipid emulsion in conventional use [48]. According to its manufacturer, Omegaven in North America is currently obtained only by applying to special access programs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the cost of omega-3 supplementation varies by dose, frequency, route of administration, and choice of formula, the leading parenteral formula used in this meta-analysis (Omegaven) has been reported to cost up to 3 times more than another lipid emulsion in conventional use [48]. According to its manufacturer, Omegaven in North America is currently obtained only by applying to special access programs.…”
Section: Discussionmentioning
confidence: 99%
“…In most instances, clinical improvement occurred approximately one month after initiation of treatment with subsequent resolution of biochemical cholestasis within 2–3 months [121,122,123,124,125,126]. While IFALD in adults is rare, several case reports have demonstrated similar reversal of cholestasis and histologic improvement upon transition from SO to FO IVLE [126,127,128]. To date, there has not been any randomized controlled trials conducted that compare equal doses of SO IVLE with FO IVLE in the treatment of pre-existing IFALD.…”
Section: Introductionmentioning
confidence: 99%
“…Similar outcomes have been reported in adults with IFALD treated with FOLE. Although fatty acid profiles were not reported in these studies, no patient was reported to have clinical signs of EFAD [47,48]. The daily requirements to prevent EFAD in adults are lower than for children.…”
Section: Human Studiesmentioning
confidence: 99%